Golden hellos: Signing bonuses for new top executives - Xu, Jin; Yang, Jun (Journal of Financial Economics, 2016)
We examine signing bonuses awarded to executives hired for or promoted to named executive officer (NEO) positions at Standard & Poor's 1500 companies during the period 1992–2011. Executive signing bonuses are sizable and increasing in use, and they are labeled by the media as “golden hellos.” We find that executive signing bonuses are mainly awarded at firms with greater information asymmetry and higher innate risks, especially to younger executives, to mitigate the executives’ concerns about termination risk. When termination concerns are strong, signing bonus awards are associated with better performance and retention outcomes.